Analysis of Information Technology Governance of the Tasikmalaya City Manpower Service Using Framework COBIT 2019 - Nurul Annisa, Tasya; Sulastri, Heni (Deparment Information System, Siliwangi University, 2023)
Currently, the success and continuity of a company or organization is very much based on IT, in terms of speed and results that can help increase the effectiveness and efficiency of business processes to achieve goals. In its implementation, the Tasikmalaya City Manpower Department had problems with software frequently occurring applications error (system failure to operate), while problems with the website was the loss and damage of information due to attacks from hackers. To overcome this, the agency does not yet have a special section that has full control over IT governance due to the lack of staff or employees who are IT experts. These problems can be identified thoroughly with governance using the COBIT 2019 framework. The form and content of the COBIT 2019 model are updated from the previous COBIT method and many new functions are added, including enabling improvements to the IT governance system. By conducting analysis, you can provide recommendations to improve the organization's capabilities to meet the agency's expectations and goals regarding IT governance in supporting its performance.Domain The COBIT 2019 used is APO and BAI with details of the APO07, APO08, APO13 and BAI08 processes. The results of measuring the capability level of the APO07 domain at the Tasikmalaya City Power Service get a capability level 3 value, the APO08 and BAI08 domains get a capability level 2 value, and the APO13 domain gets a capability level 1 value. Providing recommendations for improving the agency's information technology governance is expected to be able to carry out immediately improving the management of agency information technology so that it immediately reaches the expected level of capability.